2012
DOI: 10.1093/aje/kwr292
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Self-Reported Analgesic Use and Detection of Urinary Ibuprofen and Acetaminophen Metabolites by Means of Metabonomics: The INTERMAP Study

Abstract: Information on dietary supplements, medications, and other xenobiotics in epidemiologic surveys is usually obtained from questionnaires and is subject to recall and reporting biases. The authors used metabolite data obtained from hydrogen-1 (or proton) nuclear magnetic resonance ((1)H NMR) analysis of human urine specimens from the International Study of Macro-/Micro-Nutrients and Blood Pressure (INTERMAP Study) to validate self-reported analgesic use. Metabolic profiling of two 24-hour urine specimens per ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…Self-administration is the main cause for personal exposure (exposure in the wider environment is negligible), and large-scale, cross-sectional metabolic phenotyping studies of humans have shown a high prevalence of significant (e.g. therapeutic dose) exposure (91,92). Characterising population-level use of therapeutics (e.g.…”
Section: Exposome and Adverse Outcome Pathways: Inflammation And Ros mentioning
confidence: 99%
“…Self-administration is the main cause for personal exposure (exposure in the wider environment is negligible), and large-scale, cross-sectional metabolic phenotyping studies of humans have shown a high prevalence of significant (e.g. therapeutic dose) exposure (91,92). Characterising population-level use of therapeutics (e.g.…”
Section: Exposome and Adverse Outcome Pathways: Inflammation And Ros mentioning
confidence: 99%
“…During these visits, staff reviewed medications and recorded the medication name, self-reported duration and frequency of use (as needed or regular). Because of potential problems associated with recall and bias,11 12 we used the yearly in-person visit data to guide coding for statin use. Data related to dosage were not reported in OAI.…”
Section: Statin Treatmentmentioning
confidence: 99%
“…Within the INTERMAP, we have been successful in identification of a number of metabolites including metabolites derived from dietary and drug intake. 8487 …”
Section: Analytical Methods Developmentmentioning
confidence: 99%
“…87 We applied PCA on 1 H NMR spectra of US participants and identified 413 urine samples containing acetaminophen and its metabolites (acetaminophen users) and then applied OPLS-DA analysis on a subset of 70 urine samples from acetaminophen users and 70 urine samples from acetaminophen non-users. 86 The OPLS-DA loading coefficient plot showed that differentiation between acetaminophen users vs. non-users primarily resulted from the presence of acetaminophen and its metabolites acetaminophen glucuronide, acetaminophen sulfate, and the acetylcysteine conjugate of acetaminophen.…”
Section: Analytical Methods Developmentmentioning
confidence: 99%
See 1 more Smart Citation